A conservationist approach on environmental diagnosis of ground use in the Iguatemi river basin, Mato Grosso do Sul State, Brazil - doi: 10.4025/actascibiolsci.v34i3.9001 (Acta Scientiarum. Biological Sciences, 2012)
Landscape Ecology is a contemporary approach in conservation studies in which, coupled to the development and use of GIS-based tools, provides new methods for the analysis of forest fragments. Based on these new approaches, the environmental assessment of ground use in the Iguatemi river basin Mato Grosso do Sul State, Brazil is provided through conservation-based flora and ecology aspects. A regional map of ground use with field-collected data using Rapid Ecological Assessment methodology and digital satellite images was prepared. AER analysis showed a highly impacted region featuring intense transformation in ground use with a conversion of 87% of native forest into grazing and agriculture land. The general situation is inconsistent with APA guidelines, the conservationist unit which operates in the river basin. PPAs’ recovery, erosion control and adjustment to current environmental regulations are mandatory.